Risk Management in South African - Venter, Marli (My University, 2011)
There are currently many factors driving an increased formal focus on risk management within insurers. Risk management in insurers is particularly important as the interests of policyholders and shareholders need to be balanced. Small insurers, in particular, have problems that larger offices do not always share and risk management is therefore almost more important in the smaller companies that have fewer resources to dedicate to it. The purpose of the study was to establish the risk management practices of life insurers in South Africa and also to compare the practices of small and large insurers
MBA - WBS
Keywords: Risk management; Life insurance companies; Insurance companies